Return to play following spine surgery - Tetreault, Tyler A.; Garg, Sumeet (Frontiers in Pediatrics, 2023)
Return to physical activity is a primary concern for adolescents with idiopathic scoliosis who are indicated for spinal fusion surgery. Preoperative counseling often addresses questions regarding ability to return to sport, postoperative restrictions, time away from play, and the safety of returning to activities. Previous works have shown that flexibility can noticeably decrease after surgery, and that the ability to return to the same level of play may be impacted by the levels of the spine included in the fusion. Equipoise remains on when patients should be allowed to return to non-contact, contact, and collision play; however, there is a trend toward earlier release to activities over the last few decades. Sources agree, though, that returning to play is safe, with rare instances of complications reported for patients with spinal fusion. Here, we review the literature on the function of spinal fusion levels on flexibility and biomechanics, address factors that may influence one's recovery of sports performance, and discuss safety considerations regarding return play following spine surgery.